Conquering Leprosy - Achievements of National Leprosy Eradication Programme with Experience at National and State Level - Kollur, Lata Radhakrishna (National Journal of Community Medicine, 2014)
The study was carried out with the intention of describing the progress made by NLEP in India over decades. The study is a retrospective record based study based on data published by NLEP in National and state level reports as well as data published in WHO bulletin. There was decline in new cases of leprosy detected yearly. The prevalence rate has dropped from 4.2 in 2002 to 0.68 per 10000 in 20121.The proportion of children among new cases in year 2011-12 was which was 9.7% .Patients with visible deformity were 3%.1. On final day of 2005, India achieved its goal of elimination of leprosy as a public health problem.2